Mgnrega and Poverty Alleviation in Rural West Bengal (Trinity Journal of Management, IT & Media (TJMITM), 2023)
Whether we discuss poverty from an economic or political standpoint, it has  always been a significant concern. A developing nation is mostly assessed based  on the programmes it implements to improve the lives of its citizens. One such  nation is India, where the MGNREGA programme has been implemented as a  significant effort to reduce poverty. Since the programme has been running for  a while, we can assess its success based on how individuals have been influenced  by it or how they have reacted to it. Given the size of India’s population (which is  primarily subsistence-level, as evidenced by the epidemic), we chose to investigate  the statistics for West Bengal, a state that is more prosperous. The programme has  occasionally served as a cushion and, for some segments of the population, has  served as a life support system. According to data, the Act has assisted in reducing  poverty, but we must determine if it has also improved the lives and standards of  the population or merely stopped their decline and created stagnation. This essay  primarily examines whether West Bengal has seen any poverty reduction as a result  of MGNREGA. Our perspective is based on data that has been made available to us  by a number of sources. The findings supported the assertion that this initiative had  helped to reduce poverty. For a country like India, there must be disparity if there is  data, albeit it has decreased with time. It is up to the reader’s discretion whether they  wish to accept our findings or carry out their own research to obtain a fuller picture.
Keywords: Big data; Smart city